The Effect of Transformational Leadership on Employee Performance through Job Satisfaction as an Intervening Variable at PT. X - Ina Mery Anggitha Sinaga; Onan Marakali Siregar (Formosa Journal of Applied Sciences, 2023)
The purpose of this research is to determine the influence of transformational leadership on job satisfaction, the influence of transformational leadership on employee performance, the influence of job satisfaction on employee performance and to assess job satisfaction as an intervening variable at PT. The form of research used in this research is quantitative research with an associative approach. Sampling was carried out using probability sampling techniques using 35 respondents as samples. The results of this research show that transformational leadership has a significant effect on job satisfaction. Transformational leadership has a significant effect on employee performance, job satisfaction has a significant effect on employee performance, and leadership style has a significant effect on employee performance with job satisfaction as an intervening variable.